The Virtue of Medical Ethics Education (Res Medica, 2015)
The teaching of medical ethics in UK Medical Schools has come a long way over the last 40 years, though there remains wide variation in the quantity and content of material delivered across medical schools. Attempts to improve and standardize medical ethics teaching has come from the Institute of Medical Ethics in the form of a Consensus Statement, which details a core content of learning consistent with GMC guidance on undergraduate education. All graduating medical students must be aware of and understand the main ethical and legal issues they will face in clinical practice. However, as recent events at the Mid Staffordshire NHS Trust and Vale of Leven Hospital illustrate, medical ethics education still has a long way to go and medical educators must strive to understand what underpins moral decision making in reality. A recent appointment to develop medical ethics education locally has led me to question what an effective medical ethics education should deliver to our students. This requires rethinking what “medical ethics” means to students and, in doing so, move away from the notion of ethics as a separate discipline characterized by “dilemmas”. Whilst such cases are useful for illuminating the role of ethical theories or principles, good ethics teaching must deal with everyday ethics and all the factors that affect decision-making in reality. To do so we must find a role for avirtue-based ethics theory and the space for moral learning.